PERLINDUNGAN DAN PEMBERDAYAAN UMKM DALAM UNDANG-UNDANG NO. 10 TAHUN 2009 TENTANG KEPARIWISATAAN - Tina Savitri, Ni Nyoman; Wirawan, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 05, Juli 2013)
The main problem of the reserach presented this writing is related tothe organization of law protection and the enforcement of UMKM in theIndonesian Constitution, Undang-Undang Nomor 10 Tahun 2009. Theresearch belongs to normative law research with statue approach andanalitical conceptual approach. The result of the research shows that theUndang-Undang Nomor 10 Tahun 2009 on Tourism has organized theProtection and the Enforcement of UMKM. However, the stipulation is stillshort, insufficient, and needs to be followed kup with the formation ofRegional Regulation jfor the shake of enforcing the UMKM.
Keywords: Protection and the Enforcement, UMKM, Tourism